Risk factors associated with disease recurrence in patients with T4 staged Squamous Cell Carcinoma of the Oral Cavity treated with surgery and postoperative radiotherapy - Humayun, Nabeel Hassan; Ayub, Bushra; Qureshi, Talha Ahmed; Shaikh, Shafqat Ali; Kazi, Maliha; Usman, Rahila; Haroon, Umer Saeed (Journal of the Pakistan Medical Association, 2022)
Objective: To determine the association of clinical and pathological parameters on recurrence of treated stage T4squamous cell carcinoma of oral cavity patients managed with surgery followed by concomitant chemo and radiation therapy. Method: The retrospective, cohort study was conducted at Patel Hospital, Karachi, and comprised data of patients diagnosed with oral squamous cell carcinoma and admitted between January 1, 2014, and January 30, 2019. Patients of either gender aged 20-80 years who had a minimum follow-up of one year were included. Data was collected using the Head and Neck Cancer registry form and the medical record files. The subjects were also contacted by telephone when needed. The study end-points were disease-free survival and overall survival. Data was analysed using SPSS 21. Results: Out of the 83 patients, 65(78%) were male. The overall median(range) age was 46(20-80) years, and 43(52%) of them were aged 31-50 years. Overall, 15(18%) patients had positive margins and 48(58%) had proven cervical node metastasis on histopathology. Overall survival was 42.2% with the median(range) follow-up time was 14(9-21) months and 5-year disease-free survival was 45.8% with the median (range) follow-up time was 13(7-19). The factor that affected the final outcome was found to be the increasing nodal ratio (p=0.043). Conclusion: Among T4 oral squamous cell carcinoma patients treated with surgery and adjuvant therapy, the rate of disease recurrence was found to be high. Tumors with a high cervical nodal disease burden and/or margin involved were at substantially higher risk of recurrence. Key Words: Squamous cell carcinoma, Oral cancer, Recurrence, Survival.